COMPARATIVE BANDWITCH EVALUATION OF KERNEL WEIGHTING FUNCTION FOR PARAMETER ESTIMATION OF GEOGRAPHICALLY WEIGHTED PANEL REGRESSION MODEL - Imam Safawi Ahmad; Rosalina Monica; Maylita Hasyim (Universitas Bhinneka PGRI, 2025)
East Java Province has a fairly high economic significance, which is in second place in the province with the highest Gross Regional Domestic Product (GRDP) value in Indonesia. This is inseparable from the contribution of each district / city in the acquisition of GRDP, it is known that there are variations in the acquisition of GRDP which indicates the existence of uneven economic growth in East Java. Uneven economic growth has various risks that can affect various aspects. Therefore, it is very important to understand the factors that influence economic growth in each district/city. The Geographically Weighted Panel Regression (GWPR) approach is used to explore the dynamics of change that takes into account the spatial influence between regions. The data used in this study are data on the acquisition of GRDP at constant prices from 38 districts / cities in East Java from 2018 to 2022. The Adaptive Tricube Kernel is used in Geographically Weighted Panel Regression (GWPR) to effectively handle spatial heterogeneity in datasets where observation points are irregularly spaced. The results showed that the GWPR adaptive kernel model with an adaptive tricube kernel weighting function was the best model with R2 of 90.3% and RMSE of 1,033.8. This is in line with the concept that The tri-cube kernel is compact and has two continuous derivatives at the boundary of its support, while the another kernel has none.Adaptive kernel GWPR modelling produces different models for each district/city and produces 7 regional groups based on factors that have a significant effect. In general, there are four variables that have a significant effect on the acquisition of GRDP at constant prices in East Java, namely Regional Original Revenue (PAD), the number of workers, the number of large and medium industries, and the amount of domestic investment.